Women and videogames: What do they play? - Labrador, Francisco J.; Fernández-Arias, Ignacio; Martín-Ruipérez, Sofía; Bernaldo-de-Quirós, Mónica; Vallejo-Achón, Marina; Sánchez-Iglesias, Iván; Labrador, Marta; Estupiñá, Francisco J. (Anales de Psicología / Annals of Psychology, 2022)
The information on the use of Videogames (VG) in general samples fundamentally reflects the characteristics of men, because of their greater participation in VG, making it difficult to identify the characteristics of women and their gaming activity. Objective: To describe the gaming behaviour of adolescent and young women in Madrid, and its relation with the development of gaming problems. Method: A self-report questionnaire (Gamertest) was applied to a sample of 1,228 women (12 - 22 years old) (M = 14.84; SD = 2.469), selected by randomized sampling in schools in the Community of Madrid. Results: 51% of women admit gaming. The typical profile is a woman who plays VG sporadically and for short periods of time, preferably Action and Adventure games or Puzzles and Platforms, mainly on smartphones, at home and alone, with the purpose of having fun. The main predictive variables of gaming problems, identified with the Internet Gaming Disorder (IGD) in women are: a greater number of hours of use, playing Massively Multiplayer Online Role-Playing Game (MMORPG), and Strategy VG. The most protective factor is playing VG accompanied. The results are discussed.